Avaliação do efeito do laser terapêutico de 660nm na Leishmaniose tegumentar experimental: expressão de citocinas e perfil funcional de macrófagos - Gonçalves, Aline do Carmo (2015)
Leishmaniasis is a neglected disease, caused by protozoa of the genus Leishmania, which affects organs (visceral leishmaniasis), skin and mucous (American tegumentary leishmaniasis, ATL). The treatment of ATL is effective, however causes several collateral effects, and the absence treatment or incomplete treatment is associated with relapse. Alternative treatments should, therefore, be explored, and low potency lasers indicate the possibility of a noninvasive therapy without collateral effects and that can act together with conventional therapy. LLLT (Low-Level Laser Therapy) was applied on experimental mice BALB/c lesions, caused by Leishmania (Leishmania) amazonensis (MAB-6) in order to evaluate the healing time. The cytokines profile expression was evaluated by real-time PCR and ELISA, and Immunohistochemistry was performed to quantify M2 macrophages using MP-23 antibody. In the lesions treated with laser, it was observed a lower healing time when compared with the group of animals with untreated injuries. Moreover, it was observed an increased expression of regulatory and anti-inflammatory cytokines in the inflammatory infiltrate. We evaluated the effect of laser on macrophages RAW264.7, differentiated or not for the M1 or M2 profile, and infected in vitro. Also, we evaluated the phagocytic activity by quantification of the infected macrophages and the number of amastigotes per infected macrophage at 4 and 24 hours after infection; and nitric oxide (NO) production. The laser treatment increased the NO production and phagocytic activity of macrophages in different profiles, including those macrophages that were not differentiated before the infection. The 660nm laser stimulates macrophages and accelerates the healing of experimental injuries caused by L. amazonensis. Depending on the stage of the infection that the treatment is initiated, the laser may affect the inflammatory phase for the elimination of the parasite or stimulate the proliferative phase regulators and anti-inflammatory cytokines.